Nanotitanium Oxide Particles and Jute-Hemp Fiber Hybrid Composites: Evaluate the Mechanical, Water Absorptions, and Morphological Behaviors. (14th September 2022) - Mahesha, C. R.; Suprabha, R.; Harne, Mahesh S.; Galme, Sachin G.; Thorat, Sandeep G.; Nagabhooshanam, N.; Seikh, A. H.; Siddique, M. H.; Markos, Mebratu
Abstract : Organic fiber-based biocomposites have gained prominence in a variety of sectors over the last four to five years due to their exceptional mechanical and physical properties. Natural fiber-based composites are increasingly being employed in autos, ships, airplanes, and infrastructure projects. The current study will look at the effect of nanotitanium oxide (TiO2 ) fillers on the properties of hybridised jute-hemp-based composites. In this work, TiO2 -filled biocomposites were created using the hand layup method in hybrid jute-hemp composites containing jute fiber mats, woven hemp mats, and epoxy resin. After nanotitanium oxide fillers were injected in various weight proportions, the mechanical properties of fiber-reinforced polymers were investigated. The mechanical properties of laminated composites were tested using the ASTM standard. Compared to 2 and 4 wt.% of TiO2, the 6 wt.% was provided the highest mechanical strength. Among the different types of specimen, the E-type specimen (30 wt.% of hemp, 7 wt.% of jute, 57 wt.% of epoxy, and 6 wt.% of TiO2 ) gives their highest contribution, i.e., for tensile 24.21%, for flexural 25.03%, and for impact 24.56%. The scanning electron microscope was utilized to analyse the microstructures of nanocomposites.